2014
DOI: 10.11646/zoosymposia.9.1.7
|View full text |Cite
|
Sign up to set email alerts
|

<strong>Profundal oligochaete faunas (Annelida, Clitellata) in Japanese lakes</strong>

Abstract: Thirty-eight species of oligochaetes (Annelida, Clitellata) belonging to five families were recorded from profundal bottoms of 50 freshwater lakes on Japanese islands. They were mostly widely distributed species, and the composition of fauna is basically explained by the scheme of Timm (2012), with parallel replacement of European species. Oxygen, temperature and surrounding fauna could be main factors determining the profundal fauna in the lakes. The lumbriculids (Styloscolex japonicus, Yamaguchia toyensis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Oligochaetes L. profundicola and N. elinguis reached very high abundances in the B. Samoroda River. Euryhaline L. profundicola is known from the profundal of Lake Baikal (Timm 2012), in lakes and rivers of Kamchatka and in the southern areas of the Russian Far East (Semernoi and Sidorov 1913), Western Europe (Atanackovic et al 2013), North America (Popchenko 1988) and Japan (Ohtaka 2014).…”
Section: Faunamentioning
confidence: 99%
“…Oligochaetes L. profundicola and N. elinguis reached very high abundances in the B. Samoroda River. Euryhaline L. profundicola is known from the profundal of Lake Baikal (Timm 2012), in lakes and rivers of Kamchatka and in the southern areas of the Russian Far East (Semernoi and Sidorov 1913), Western Europe (Atanackovic et al 2013), North America (Popchenko 1988) and Japan (Ohtaka 2014).…”
Section: Faunamentioning
confidence: 99%
“…Stable isotopic compositions of oligochaetes were measured without species identification in the present study. Previous studies showed a total of 13 species of oligochaetes were observed in Lake Kasumigaura (Ohtaka 2014), and their life cycles and ecological behaviors were different among species (e.g., Carroll and Dorris 1972; Yasuda and Okino 1987; Ohtaka 1992; Ohtaka and Kikuchi 1997), suggesting interspecific differences may affect variability of δ 13 C and δ 15 N. In future studies, interspecific differences of methane‐derived carbon contributions should be examined to understand ecological roles of oligochaetes in methane dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…3.3.2 Hrabea ogumai Yamaguchi, 1936(Yamaguchi 1936a, 1953Fend & Ohtaka 2004) *Lamprortus orientalis 3.1 New record Lumbriculus multiatriatus Yamaguchi, 1937(Yamaguchi 1937a, 1953, Cook 1971, Sokolskaya 1972a, Timm & Rodriguez 1994, Timm 1999) Lumbriculus japonicus Yamaguchi, 1936(Yamaguchi 1953, Timm 1997, 1999 =Lumbriculus variegatus japonicus Yamaguchi, 1936(Cook 1971) Lumbriculus mukoensis Yamaguchi,1953(Timm 1997, 1999, Torii & Ohtaka 2007 =Lumbriculus variegatus mukoensis Yamaguchi, 1953(Cook 1971) Lumbriculus variegatus (Müller, 1774) (Yamaguchi 1953) Rhynchelmis orientalis Yamaguchi, 1936(Cook 1971, Kaygorodova & Liventseva 2007, Fend & Brinkhurst 2010, Fend & Lenat 2010) Styloscolex (Styloscolex) japonicus Yamaguchi, 1937 = Styloscolex japonicus Yamaguchi, 1937(Yamaguchi 1937b, 1953, Cook 1971, Ohtaka 2014, Sokolskaya 1976, Timm 1997, 1999, Timm & Všivkova 2007, Rodriguez et al 2014) *Styloscolex (Styloscolex) tazawaensis n. sp.…”
Section: Taxonomymentioning
confidence: 99%
“…The Japanese records and descriptions are largely the work of Hideji Yamaguchi (1936aYamaguchi ( , 1936bYamaguchi ( , 1937aYamaguchi ( , 1937bYamaguchi ( , 1953, who described 6 endemic species, including the monotypic Hrabea ogumai Yamaguchi, 1936, and also reported the apparently cosmopolitan Lumbriculus variegatus (Müller, 1774). Since then, additional lumbriculid distribution records have been presented by Ohtaka & Nishino (1995), Torii & Ohtaka (2007), Fend & Brinkhurst (2010) and Ohtaka (2014); and a single new species, Yamaguchia toyensis Fend & Ohtaka, 2004, has been described.…”
Section: Introductionmentioning
confidence: 99%